Analisis Pengaruh Panjang Sirip Heatsink Terhadap Produksi Air Kondensasi pada Alat Pengahasil Air Atmosfir - Erkes Lodoh; Muhamad Jafri; Ben V. Tarigan (Jurusan Teknik Mesin, Fakultas Sains dan Teknik, Universitas Nusa Cendana, 2021)
This study aims to determine the effect of heat sink fin length oriented at 700 on the production of atmospheric air condensation water. The method used is an experimental method of 3 converters with variations in the length of the heat sink; 8 cm, 10 cm and 12 cm. The three sizes of these heat sinks are that the length of the heat sink affects the distribution of environmental temperature, the temperature on the cold side of the heat sink, the temperature on the hot side of the heat sink, the temperature in the condensing chamber and the volume of condensed water. From the third study, the best size was the length of the 12 cm heat sink with a water production of 26.9 ml/24h.